Cross-linked zwitterionic modified adsorbent, ultra-high cross-linked zwitterionic modified adsorbent, preparation methods of cross-linked zwitterionic modified adsorbent and ultra-high cross-linked zwitterionic modified adsorbent and blood perfusion device

Through cross-linking copolymerization and post-crosslinking technology, zwitterion-modified adsorbents with super-hydrophilicity and excellent adsorption properties were prepared, which solved the problem of large protein adsorption caused by the hydrophobicity of polystyrene macroporous resins and improved blood The adsorption efficiency and compatibility of the perfusion device are suitable for the removal of various toxins.

CN119192666APending Publication Date: 2024-12-27QUANZHOU NORMAL UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411345117.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Polystyrene macroporous adsorption resin has strong hydrophobicity in blood perfusion applications, resulting in large amount of protein adsorption, reducing adsorption efficiency and blood compatibility. The existing modification process is cumbersome and difficult to simplify.

Method used

By cross-linking and copolymerizing styrene monomers with epoxy-containing monomers, introducing epoxy groups and reacting with amino compounds, further quaternization is formed to form a cross-linked zwitterionic modified adsorbent, and its hydrophilicity is improved and adsorption properties, and post-crosslinking by small molecule crosslinking agents, optimize structure and performance.

Benefits of technology

The prepared crosslinked zwitterion modified adsorbent has super hydrophilicity, ultra-low protein adsorption and excellent blood compatibility. It has good adsorption properties for toxins. It has simple process and is suitable for removing urinary dysfunction in blood perfusion devices. toxins and other toxins associated with liver failure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192666A_ABST
    Figure CN119192666A_ABST
Patent Text Reader

Abstract

The invention provides a cross-linked zwitter-ion modified adsorbent, an ultra-high cross-linked zwitter-ion modified adsorbent, a preparation method of the ultra-high cross-linked zwitter-ion modified adsorbent and a blood perfusion device, and belongs to the technical field of adsorption resin. The preparation method comprises the following steps: carrying out cross-linking copolymerization on a styrene monomer and an epoxy group-containing monomer, introducing an epoxy group to an adsorbent structure, introducing a tertiary amine group by utilizing the reaction of the epoxy group and an amino compound, and further reacting with a quaternization reagent to quaternize the tertiary amine structure, thereby obtaining the modified adsorbent containing the zwitterionic group. Due to the super-hydrophilicity of zwitterionic groups, zwitterions are introduced into the compound structure of the adsorbent to realize the hydrophilicity of the adsorbent, the protein adsorbability is reduced, and the preparation method is simple in process; after the cross-linked zwitter-ion modified adsorbent is obtained, the cross-linked zwitter-ion modified adsorbent is cross-linked by using a small molecule cross-linking agent, and the surface group structure and pore structure of the adsorbent can be changed, so that the adsorption performance of the adsorbent on toxin, the adsorption and slow release performance of heparin, the blood compatibility and the like are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adsorption resins, and in particular relates to a cross-linked zwitterion-modified adsorbent and an ultra-high cross-linked zwitterion-modified adsorbent and a preparation method thereof, and a blood perfusion device. Background Art

[0002] Hemoperfusion adsorption therapy is an extracorporeal blood purification treatment technology, mainly used to treat certain intractable diseases. It is a process of removing harmful substances from the blood by drawing the patient's blood out of the body, filtering it through a special adsorption column, and then returning the purified blood to the patient's body. Common adsorption materials in hemoperfusion adsorption columns include activated carbon, resin, etc. These materials can adsorb and remove harmful substances such as toxins, metabolites, immune complexes, etc. in the blood. After adsorption treatment, these harmful substances are effectively removed, which can improve the patient's condition.

[0003] As a common hemoperfusion adsorption material, polystyrene macroporous adsorption resin has made significant progress in the application of hemoperfusion in recent years. Due to its structural advantages, polystyrene macroporous adsorption resin shows excellent adsorption performance, especially in the removal of medium and large molecular toxins. However, in clinical treatment and scientific research experiments, it was found that polystyrene macroporous adsorption resin hemoperfusion adsorbents generally have the problem of strong hydrophobicity, that is, poor hydrophilicity. The hydrophobicity of the adsorption resin easily leads to the problem of large protein adsorption of the material, which in turn will cause many adverse effects, such as the adsorbent material will be covered by a large amount of protein, reducing the adsorption efficiency of the target substance; the large amount of adsorbent protein adsorption will lead to poor blood compatibility of the adsorbent, causing clinical treatment risks; in addition, the loss of protein in blood or plasma will have an adverse effect on the patient's body. Therefore, how to solve the problems of poor hydrophilicity of adsorbent materials and the large amount of protein adsorption caused by them is an important research direction in the field of hemoperfusion adsorbent materials.

[0004] Zwitterionic compounds of biomimetic cell membrane structures, because zwitterionic groups have both positive and negative charge centers, enable them to form strong hydrogen bonds with water molecules, thereby showing superhydrophilic properties. The superhydrophilicity of these zwitterionic groups enables a hydration layer to be formed on the surface of the biomimetic cell membrane, which helps to improve the biocompatibility or blood compatibility of the material and reduce protein adsorption or adhesion of other tissue components. Patent CN105348541B uses the RAFT free radical polymerization method to prepare mixed charge zwitterionic polymers, and then grafts them to the surface of polystyrene resins through reduction reactions and click chemistry methods to achieve hydrophilic modification of the surface of polystyrene adsorption resins and improve the blood compatibility of adsorption resins; however, its polymer preparation process and grafting modification process are relatively cumbersome, and there are still disadvantages that are not conducive to practical applications. Therefore, how to simplify the process and improve the adsorption performance of the adsorbent has become a technical problem that needs to be solved in the prior art. Summary of the invention

[0005] The purpose of the present invention is to provide a cross-linked zwitterion modified adsorbent and an ultra-high cross-linked zwitterion modified adsorbent and a preparation method thereof and a blood perfusion device. The preparation method provided by the present invention has a simple process, and the prepared adsorbent has excellent hydrophilicity and ultra-low protein adsorption performance.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a cross-linked zwitterion modified adsorbent, comprising the following steps:

[0008] (1) mixing a styrene monomer, an epoxy group-containing monomer, a porogen and an initiator to obtain an oil phase;

[0009] (2) mixing the dispersant and water to obtain an aqueous phase;

[0010] (3) mixing the oil phase obtained in step (1) and the water phase obtained in step (2) to carry out suspension polymerization to obtain a cross-linked porous resin containing epoxy groups;

[0011] (4) mixing the epoxy group-containing cross-linked porous resin obtained in step (3), the first solvent and the amino compound, and performing a ring-opening addition reaction to obtain a tertiary amine group-containing cross-linked porous resin;

[0012] (5) mixing the cross-linked porous resin containing tertiary amine groups obtained in step (4), a second solvent and a quaternary ammonium reagent, and performing a quaternary ammonium reaction to obtain a cross-linked zwitterion-modified adsorbent;

[0013] There is no chronological order for steps (1) and (2).

[0014] Preferably, in step (1), the mass ratio of the styrene monomer, the epoxy-containing monomer, the porogen and the initiator is 1: (0.05-1): (0.3-3): (0.005-0.05).

[0015] Preferably, in step (2), the mass ratio of water to dispersant is 1:(0.001-0.06).

[0016] Preferably, in step (3), the mass ratio of the oil phase to the water phase is 1:(1-5).

[0017] Preferably, the suspension polymerization temperature in step (3) is 60 to 90° C., and the suspension polymerization time is 4 to 24 hours.

[0018] Preferably, the temperature of the ring-opening addition reaction in step (4) is 20 to 80° C., and the time of the ring-opening addition reaction is 1 to 48 hours.

[0019] The present invention also provides a cross-linked zwitterion modified adsorbent prepared by the preparation method described in the above technical solution.

[0020] The present invention also provides a method for preparing an ultra-high cross-linked zwitterion modified adsorbent, comprising the following steps: mixing the cross-linked zwitterion modified adsorbent described in the above technical scheme, a small molecule cross-linking agent, a third solvent and a catalyst, and performing a post-cross-linking reaction to obtain the ultra-high cross-linked zwitterion modified adsorbent.

[0021] The present invention also provides an ultra-high cross-linked zwitterion modified adsorbent prepared by the preparation method described in the above technical solution.

[0022] The present invention also provides a blood perfusion device, comprising the cross-linked zwitterion modified adsorbent described in the above technical solution or the ultra-high cross-linked zwitterion modified adsorbent described in the above technical solution.

[0023] The present invention provides a method for preparing a cross-linked zwitterion modified adsorbent, comprising the following steps:

[0024] (1) mixing a styrene monomer, an epoxy group-containing monomer, a porogen and an initiator to obtain an oil phase; (2) mixing a dispersant and water to obtain an aqueous phase; (3) mixing the oil phase obtained in step (1) and the aqueous phase obtained in step (2) to carry out suspension polymerization to obtain a cross-linked porous resin containing epoxy groups; (4) mixing the cross-linked porous resin containing epoxy groups obtained in step (3), a first solvent and an amino compound to carry out a ring-opening addition reaction to obtain a cross-linked porous resin containing tertiary amine groups; (5) mixing the cross-linked porous resin containing tertiary amine groups obtained in step (4), a second solvent and a quaternizing agent to carry out a quaternizing reaction to obtain a cross-linked zwitterion modified adsorbent; there is no chronological order for steps (1) and (2). The present invention crosslinks and copolymerizes styrene monomers and epoxy-containing monomers, introduces epoxy groups into the adsorbent structure, introduces tertiary amine groups by reacting the epoxy groups with amino compounds, and further reacts with a quaternizing agent to quaternize the tertiary amine structure to obtain an adsorbent modified with zwitterionic groups. Due to the superhydrophilicity of the zwitterionic groups, zwitterions are introduced into the compound structure of the adsorbent to achieve the hydrophilicity of the adsorbent, reduce protein adsorption, and the preparation method is simple; after obtaining the crosslinked zwitterionic modified adsorbent, it is crosslinked with a small molecule crosslinking agent to change the surface group structure and pore structure of the adsorbent, thereby improving the adsorption performance of the adsorbent to toxins (protein-bound toxinoids, macromolecular toxins), the adsorption and sustained release performance of heparin, blood compatibility, etc. The results of the embodiment show that the crosslinked zwitterionic modified adsorbent prepared by the present invention has superhydrophilicity, ultra-low protein adsorption, excellent blood compatibility, and excellent adsorption to toxins. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a microscopic appearance picture of the cross-linked porous resin containing epoxy groups prepared in step (3) of Example 1 of the present invention;

[0026] Figure 2 This is a microscopic appearance picture of the cross-linked zwitterion modified adsorbent prepared in Example 1 of the present invention;

[0027] Figure 3 This is the infrared spectrum of the cross-linked zwitterion modified adsorbent prepared in Example 1 of the present invention;

[0028] Figure 4 This is a microscopic appearance picture of the ultra-high cross-linked zwitterion modified adsorbent prepared in Example 6 of the present invention;

[0029] Figure 5 This is a microscopic appearance picture of the ultra-high cross-linked zwitterion modified adsorbent prepared in Example 10 of the present invention. DETAILED DESCRIPTION

[0030] The present invention provides a method for preparing a cross-linked zwitterion modified adsorbent, comprising the following steps:

[0031] (1) mixing a styrene monomer, an epoxy group-containing monomer, a porogen and an initiator to obtain an oil phase;

[0032] (2) mixing the dispersant and water to obtain an aqueous phase;

[0033] (3) mixing the oil phase obtained in step (1) and the water phase obtained in step (2) to carry out suspension polymerization to obtain a cross-linked porous resin containing epoxy groups;

[0034] (4) mixing the epoxy group-containing cross-linked porous resin obtained in step (3), the first solvent and the amino compound, and performing a ring-opening addition reaction to obtain a tertiary amine group-containing cross-linked porous resin;

[0035] (5) mixing the cross-linked porous resin containing tertiary amine groups obtained in step (4), a second solvent and a quaternary ammonium reagent, and performing a quaternary ammonium reaction to obtain a cross-linked zwitterion-modified adsorbent;

[0036] There is no chronological order for steps (1) and (2).

[0037] Unless otherwise specified, the present invention has no particular limitation on the sources of the raw materials, and commercially available products known to those skilled in the art may be used.

[0038] The invention mixes styrene monomers, epoxy-containing monomers, porogens and initiators to obtain an oil phase.

[0039] In the present invention, the styrene-based monomer preferably includes at least one of a polyvinyl aromatic monomer and a monovinyl aromatic monomer.

[0040] In the present invention, the polyvinyl aromatic monomer preferably includes one or more of divinylbenzene, meta-divinylbenzene, para-divinylbenzene, trivinylbenzene, divinyltoluene, divinylxylene, divinylnaphthalene and their derivatives; the derivatives are preferably halides, more preferably chlorinated compounds.

[0041] In the present invention, the monovinyl aromatic monomer preferably includes one or more of styrene, C1-C4 alkyl-substituted styrene and derivatives thereof; the C1-C4 alkyl-substituted styrene preferably includes one or more of ethylstyrene, m-ethylstyrene and p-ethylstyrene and derivatives thereof; the derivative is preferably a halogenated compound, more preferably a chlorinated compound.

[0042] In the present invention, the epoxy group-containing monomer preferably includes at least one of glycidyl methacrylate and glycidyl acrylate.

[0043] In the present invention, the porogen preferably includes at least one of benzene, toluene, xylene, ethylbenzene, methyl isobutyl carbinol, diisobutyl carbinol, isooctyl alcohol, n-heptane, cycloalkane, paraffin, methyl silicone oil and industrial white oil.

[0044] In the present invention, the initiator is preferably an oily initiator; the oily initiator preferably includes at least one of a peroxide and an azo compound, and more preferably benzoyl peroxide or azobisisobutyronitrile.

[0045] In the present invention, the mass ratio of the styrene monomer, the epoxy-containing monomer, the porogen and the initiator is preferably 1: (0.05-1): (0.3-3): (0.005-0.05). As an embodiment, the mass ratio of the styrene monomer, the epoxy-containing monomer, the porogen and the initiator may be 1: (0.05-0.8): (0.5-2): (0.01-0.04). The present invention limits the mass ratio of the styrene monomer, the epoxy-containing monomer, the porogen and the initiator to the above range, and adjusts the grafting amount of the zwitterionic group by adjusting the content of the epoxy group, and at the same time adjusts the pore structure of the adsorbent, thereby further improving the hydrophilicity and adsorption of the adsorbent.

[0046] The present invention has no special limitation on the mixing operation of the styrene monomer, epoxy-containing monomer, porogen and initiator. The raw materials can be uniformly mixed using a mixing technical scheme well known to those skilled in the art.

[0047] The present invention mixes the dispersant and water to obtain an aqueous phase.

[0048] In the present invention, the dispersant preferably includes at least one of polyvinyl alcohol, gelatin and cellulose derivatives. In the present invention, the average molecular weight of the polyvinyl alcohol is preferably 20,000 to 300,000 g / mol; the grade of the polyvinyl alcohol is preferably 1788, 1750, 1799, 2488, 2498, 2688, 117 or 98-99.

[0049] In the present invention, the mass ratio of water to dispersant is preferably 1:(0.001-0.06). As an embodiment, the mass ratio of water to dispersant may be 1:(0.005-0.06), or 1:(0.01-0.05). The present invention limits the mass ratio of water to dispersant within the above range, so that the dispersant can be dissolved more fully.

[0050] The present invention has no special limitation on the mixing operation of the dispersant and water, and the raw materials can be uniformly mixed using a mixing technical solution well known to those skilled in the art.

[0051] After obtaining the oil phase and the water phase, the present invention mixes the oil phase and the water phase and performs suspension polymerization to obtain a cross-linked porous resin containing epoxy groups.

[0052] In the present invention, the mass ratio of the oil phase to the water phase is preferably 1:(1-5). As an embodiment, the mass ratio of the oil phase to the water phase can be 1:(1.5-4) or 1:(2-3). The present invention limits the mass ratio of the oil phase to the water phase within the above range, which can make the product obtained by polymerization have a smaller particle size.

[0053] In the present invention, the temperature of the suspension polymerization is preferably 60 to 90° C. As an embodiment, the temperature of the suspension polymerization may be 70 to 85° C.

[0054] In the present invention, the suspension polymerization time is preferably 4 to 24 hours. As an embodiment, the suspension polymerization time can be 5 to 20 hours, or 10 to 15 hours. The present invention limits the suspension polymerization temperature and time within the above ranges, so that the polymerization reaction can be fully carried out.

[0055] After the suspension polymerization is completed, the present invention preferably purifies and dries the product of the suspension polymerization in sequence to obtain a cross-linked porous resin containing epoxy groups.

[0056] In the present invention, the purification is preferably washing; the detergent during the washing is preferably an ethanol solution; the volume concentration of the ethanol solution is preferably 70-100%; the number of washings is preferably 3-8 times; the time for each washing is preferably 2-4 hours, more preferably 3 hours; and the washing is preferably carried out under stirring conditions.

[0057] In the present invention, the drying temperature is preferably 40 to 80° C. The present invention has no particular limitation on the drying time, as long as the product is sufficiently dried. In the present invention, the drying preferably includes hot air drying or vacuum heating.

[0058] After obtaining the cross-linked porous resin containing epoxy groups, the present invention mixes the cross-linked porous resin containing epoxy groups, a first solvent and an amino compound to perform a ring-opening addition reaction to obtain a cross-linked porous resin containing tertiary amine groups.

[0059] In the present invention, the first solvent preferably includes at least one of water, ethanol, methanol and acetone.

[0060] In the present invention, the amino compound preferably includes at least one of N,N-dimethyl-1,3-propylenediamine, N,N-dimethylaminoethylamine, N,N-diethylaminopropylamine and polyethyleneimine, and more preferably polyethyleneimine. The present invention uses polyethyleneimine as the amino compound, and after quaternization reaction, the prepared cross-linked zwitterion modified adsorbent not only has excellent hydrophilicity, but also has good adsorption performance for uremic protein-bound toxins (indoxyl sulfate IS, p-cresol sulfate PCS, indoleacetic acid IAA, hippuric acid HA, etc.) and hepatovirins (bilirubin, bile acid, etc.).

[0061] In the present invention, the mass ratio of the epoxy group-containing cross-linked porous resin, the first solvent and the amino compound is preferably 1: (1-10): (0.1-1). As an embodiment, the mass ratio of the epoxy group-containing cross-linked porous resin, the first solvent and the amino compound can be 1: (2-8): (0.1-0.8), or 1: (3-6): (0.2-0.6). The present invention limits the mass ratio of the epoxy group-containing cross-linked porous resin, the first solvent and the amino compound to the above range, which can introduce more tertiary amine groups, introduce more zwitterionic groups in the subsequent reaction process, and further improve the hydrophilicity and other properties of the adsorbent.

[0062] In the present invention, the temperature of the ring-opening addition reaction is preferably 20 to 80° C. As an embodiment, the temperature of the ring-opening addition reaction can be 30 to 70° C., or 40 to 60° C.

[0063] In the present invention, the time of the ring-opening addition reaction is preferably 1 to 48 hours. As an embodiment, the time of the ring-opening addition reaction can be 5 to 40 hours, or 10 to 30 hours. The present invention limits the temperature and time of the ring-opening addition reaction to the above range, so that the reaction can be fully carried out, and the hydrophilicity and other properties of the adsorbent can be further improved.

[0064] After the ring-opening addition reaction is completed, the product of the ring-opening addition reaction is preferably purified to obtain a cross-linked porous resin containing tertiary amine groups.

[0065] In the present invention, the purification is preferably performed sequentially by washing with water and washing with an ethanol solution.

[0066] In the present invention, the water used in the water washing is preferably pure water; the number of the water washing is preferably 3 to 5 times; the time of each water washing is preferably 2 to 4 hours; and the water washing is preferably carried out under stirring conditions.

[0067] In the present invention, the volume concentration of the ethanol solution is preferably 70-100%; the number of times of washing with the ethanol solution is preferably 3-5 times; the time of each washing with the ethanol solution is preferably 2-4 hours; and the washing with the ethanol solution is preferably carried out under stirring conditions.

[0068] A cross-linked porous resin containing tertiary amine groups is obtained. The present invention mixes the cross-linked porous resin containing tertiary amine groups, a second solvent and a quaternary ammonium reagent to carry out a quaternary ammonium reaction to obtain a cross-linked zwitterion modified adsorbent.

[0069] In the present invention, the second solvent preferably includes at least one of water, ethanol, methanol, acetone and ethyl acetate.

[0070] In the present invention, the quaternizing agent preferably includes at least one of sultone, alkane lactone and sodium chloroacetate; the sultone preferably includes at least one of 1,3-propane sultone, 1,4-butane sultone and 2,4-butane sultone; the alkane lactone preferably includes at least one of β-propiolactone and 1,4-butyrolactone.

[0071] In the present invention, the mass ratio of the cross-linked porous resin containing tertiary amine groups, the second solvent and the quaternary ammonium reagent is preferably 1: (1-10): (0.1-1). As an embodiment, the mass ratio of the cross-linked porous resin containing tertiary amine groups, the second solvent and the quaternary ammonium reagent can be 1: (2-9): (0.2-0.8), or 1: (3-7): (0.4-0.6). The present invention limits the mass ratio of the cross-linked porous resin containing tertiary amine groups, the second solvent and the quaternary ammonium reagent to the above range, which can introduce more zwitterionic groups and further improve the hydrophilicity and other properties of the adsorbent.

[0072] In the present invention, the temperature of the quaternization reaction is preferably 10 to 80° C. As an embodiment, the temperature of the quaternization reaction can be 20 to 70° C., or 30 to 60° C.

[0073] In the present invention, the time of the quaternization reaction is preferably 1 to 24 hours. As an embodiment, the time of the quaternization reaction can be 5 to 20 hours, or 10 to 15 hours. The present invention limits the temperature and time of the quaternization reaction to the above range, so that the quaternization reaction can be fully carried out.

[0074] After the quaternization reaction is completed, the present invention preferably purifies and dries the product of the quaternization reaction in sequence to obtain a cross-linked zwitterion-modified adsorbent.

[0075] In the present invention, the purification is preferably washing; the detergent during the washing is preferably an ethanol solution; the volume concentration of the ethanol solution is preferably 70-100%; the number of washings is preferably 3-5 times; the time for each washing is preferably 2-4 hours, more preferably 3 hours; and the washing is preferably carried out under stirring conditions.

[0076] In the present invention, the drying temperature is preferably 40 to 80° C. The present invention has no particular limitation on the drying time, as long as the product is sufficiently dried. In the present invention, the drying preferably includes hot air drying or vacuum heating.

[0077] The present invention crosslinks and copolymerizes styrene monomers and epoxy monomers, introduces epoxy groups into the resin adsorbent structure, uses the chemical reaction between epoxy groups and amino groups in amino compounds to introduce tertiary amine group structures, and further quaternizes the tertiary amine structure to obtain a resin adsorbent modified with zwitterionic groups. The present invention regulates the amount of grafting of zwitterionic groups by the content of epoxy groups, and further controls the hydrophilicity; due to the super-hydrophilicity of zwitterionic groups, a small amount of zwitterions are introduced into the chemical structure of the resin adsorbent to achieve the hydrophilicity of the resin adsorbent; in the preparation of epoxy-group-containing crosslinked porous resins, the amount of epoxy monomers is controlled within 5% to introduce zwitterionic groups, and the excellent hydrophilicity of the resin adsorbent can be achieved, and the preparation method is simple.

[0078] The present invention also provides a cross-linked zwitterion modified adsorbent prepared by the preparation method described in the above technical solution.

[0079] The cross-linked zwitterion modified adsorbent prepared by the present invention has excellent hydrophilicity and ultra-low protein adsorption, and has good adsorption performance for toxins.

[0080] The present invention also provides a method for preparing an ultra-high cross-linked zwitterion modified adsorbent, comprising the following steps: mixing the cross-linked zwitterion modified adsorbent described in the above technical scheme, a small molecule cross-linking agent, a third solvent and a catalyst, and performing a post-cross-linking reaction to obtain the ultra-high cross-linked zwitterion modified adsorbent.

[0081] In the present invention, the small molecule crosslinking agent preferably includes 4-aminobutyraldehyde dimethyl acetal, aminoacetaldehyde dimethyl acetal, aminoacetaldehyde diethyl acetal, methylaminoacetaldehyde dimethyl acetal, N,N-dimethylformamide dimethyl acetal, N,N-dimethylformamide diethyl acetal, N,N-dimethylformamide diisopropyl acetal, ethanolaldehyde diethyl acetal, 4,4-(dimethylamino)butyraldehyde diethyl acetal, (S)-2-hydroxypropionaldehyde dimethoxyacetal, succinaldehyde bis(dimethyl acetal), ethoxyacetaldehyde At least one of diethyl acetal, acetaldehyde diethyl acetal, butyraldehyde diethyl acetal, nonanal dimethyl acetal, citral dimethyl acetal, benzaldehyde diethyl acetal, isobutyraldehyde diethyl acetal, 2-chloroacetaldehyde dimethyl acetal, benzaldehyde dimethyl acetal, propionaldehyde dimethyl acetal, propionaldehyde diethyl acetal, phenylacetaldehyde dimethyl acetal, 1,1,3,3-tetraethoxypropane, 1,1,3,3-tetramethoxypropane, triethyl orthoformate, trimethyl orthoformate, formaldehyde dimethyl acetal and diethoxymethane. The present invention uses a small molecule cross-linking agent to cross-link the cross-linked zwitterionic modified adsorbent, which can further regulate the chemical properties and physical structure of the cross-linked zwitterionic modified adsorbent, and then regulate the blood compatibility of the adsorbent and the target toxin adsorption performance. Taking diethoxymethane as an example, the use of diethoxymethane to crosslink and modify the crosslinked zwitterion modified adsorbent can regulate the BET parameters of the pore structure of the resin adsorbent, and can also change the group structure on the surface of the resin adsorbent, such as introducing oxygen-containing groups, etc.; taking 4-aminobutyraldehyde dimethyl acetal as an example, the use of 4-aminobutyraldehyde dimethyl acetal to crosslink and modify the crosslinked zwitterion modified adsorbent can change the pore structure characteristics of the resin on the one hand, and on the other hand, introduce amino groups into the structure of the resin adsorbent, thereby giving the resin adsorbent special chemical properties and adsorption properties. Introducing polar groups such as amino groups into the chemical structure of the adsorbent can change the polarity and charge of the adsorbent, which in turn affects the adsorption performance of the adsorbent for protein-bound toxins (uremic protein-bound toxins, bilirubin, etc.), the adsorption and sustained release performance of heparin, the adsorption performance of medium and large molecular toxins, blood compatibility, etc.

[0082] In the present invention, the third solvent preferably includes at least one of ethylene dichloride, methylene chloride and nitrobenzene.

[0083] In the present invention, the catalyst preferably includes at least one of ferric chloride, aluminum chloride and zinc chloride.

[0084] In the present invention, the mass ratio of the cross-linked zwitterion modified adsorbent, the small molecule cross-linking agent, the third solvent and the catalyst is preferably 1: (0.01-2): (1-10): (0.02-2). As an embodiment, the mass ratio of the cross-linked zwitterion modified adsorbent, the small molecule cross-linking agent, the third solvent and the catalyst can be 1: (0.05-1.5): (2-8): (0.05-1.5), or 1: (0.05-1.5): (4-6): (0.05-1.5). The present invention limits the mass ratio of the cross-linked zwitterion modified adsorbent, the small molecule cross-linking agent, the third solvent and the catalyst to the above range, which can adjust the chemical properties and physical structure of the ultra-high cross-linked zwitterion modified adsorbent, and further improve the blood compatibility of the adsorbent and the adsorption performance of toxins.

[0085] In the present invention, the temperature of the post-crosslinking reaction is preferably 50 to 100° C. As an embodiment, the temperature of the post-crosslinking reaction may be 60 to 90° C., or 70 to 80° C.

[0086] In the present invention, the time of the post-crosslinking reaction is preferably 3 to 48 hours. As an embodiment, the time of the post-crosslinking reaction can be 5 to 40 hours, or 10 to 30 hours. The present invention limits the temperature and time of the post-crosslinking reaction to the above range, so that the reaction can be fully carried out.

[0087] After the post-crosslinking reaction is completed, the present invention preferably purifies and dries the product of the post-crosslinking reaction in sequence to obtain an ultra-high crosslinking zwitterion modified adsorbent.

[0088] In the present invention, the purification is preferably: first, use a hydrochloric acid solution with a mass concentration of 0.2-8% to stir and wash for 1-24 hours, then use a sodium hydroxide solution with a mass concentration of 0.5-5% to stir and wash for 1-24 hours, then wash with water until neutral, and finally use an ethanol solution with a volume concentration of 70-100% to rinse for 2-10 hours.

[0089] In the present invention, the drying temperature is preferably 40 to 80° C. The present invention has no particular limitation on the drying time, as long as the product is sufficiently dried. In the present invention, the drying preferably includes hot air drying or vacuum heating.

[0090] The present invention also provides an ultra-high cross-linked zwitterion modified adsorbent prepared by the preparation method described in the above technical solution.

[0091] The ultra-high cross-linked zwitterion modified adsorbent prepared by the invention has excellent hydrophilicity, ultra-low protein adsorption, excellent blood compatibility and excellent adsorption to toxins.

[0092] In the present invention, the reaction conditions of the suspension polymerization preparation of epoxy group-containing cross-linked porous resin, the modified preparation of cross-linked zwitterion-modified adsorbent, and the post-cross-linking preparation of ultra-high cross-linked zwitterion-modified adsorbent have an impact on the surface physicochemical properties, pore structure (specific surface area, average pore size and pore volume, etc.) of the product, and the adsorption performance of toxins or proteins. The suspension polymerization preparation conditions include the type and content of the added polymerization monomer, the degree of cross-linking, the type and amount of the porogen; the modification preparation conditions of the cross-linked zwitterion-modified adsorbent include the weight and amount of the modifier, the type of reaction medium, the reaction time and the reaction temperature, etc.; the post-cross-linking reaction conditions include the type and content of the catalyst, the type and content of the cross-linking agent, the reaction time and the reaction temperature, etc. By appropriately changing the reaction conditions, the structure and performance of the adsorbent can be effectively regulated to obtain the target product with ideal performance; the preparation method provided by the present invention has a simple process, the structure and performance of the adsorbent are controllable, and it has a strong practical application value. The preparation of the adsorbent helps to reduce the protein adsorption performance of the adsorbent material, improve the blood compatibility and clinical treatment effectiveness of the adsorbent, and reduce the risk of clinical treatment.

[0093] The present invention also provides a blood perfusion device, comprising the cross-linked zwitterion modified adsorbent described in the above technical solution or the ultra-high cross-linked zwitterion modified adsorbent described in the above technical solution.

[0094] The cross-linked zwitterion modified adsorbent and the ultra-high cross-linked zwitterion modified adsorbent prepared by the invention can be used as adsorbents in a blood perfusion device to adsorb endogenous or exogenous poisons or pathogenic substances in human or animal bodies during blood perfusion.

[0095] The cross-linked zwitterion modified adsorbent and the ultra-high cross-linked zwitterion modified adsorbent prepared by the present invention can adsorb and remove uremic toxins (urea, creatinine, macromolecular toxins in uremic diseases, uremic protein-bound toxins, etc.), bilirubin and other toxins related to liver failure, bacterial toxins, inflammatory mediators, autoantibodies and immune complexes, high lipoproteins, etc. The perfusion device for removing endogenous or exogenous poisons or pathogenic substances in the blood of the present invention can be used for the clinical treatment of diseases and conditions such as renal failure, liver failure, acute poisoning, sepsis and septicemia, autoimmune diseases, inflammatory diseases, hyperlipidemia, etc. These applications are all based on the fact that the blood perfusion device of the present invention can effectively remove harmful substances in the body, thereby providing significant therapeutic effects in emergency situations or as an auxiliary treatment method.

[0096] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0097] Example 1

[0098] (1) 100 g of divinylbenzene (DVB 80), 5 g of glycidyl methacrylate, 160 g of a porogen (80 g of toluene, 80 g of n-heptane) and 2 g of benzoyl peroxide were mixed to obtain an oil phase, wherein the mass ratio of divinylbenzene, glycidyl methacrylate, porogen and benzoyl peroxide was 1:0.05:1.6:0.02;

[0099] (2) mixing 400 g of water and 10 g of gelatin to obtain an aqueous phase, wherein the mass ratio of water to gelatin is 1:0.025;

[0100] (3) adding the oil phase obtained in step (1) to the water phase obtained in step (2) (the mass ratio of the oil phase to the water phase is 1:1.5), and performing suspension polymerization at 80° C. for 12 h. After the reaction is completed, stirring and washing with a 95% by volume ethanol solution for 5 times, each time for 3 h, and then drying at 70° C. to obtain a cross-linked porous resin containing epoxy groups;

[0101] (4) 100 g of the epoxy group-containing cross-linked porous resin prepared in step (3) was mixed with 400 g of water, 10 g of N, N-dimethyl-1, 3-propylenediamine was added, and a ring-opening addition reaction was carried out at 80° C. for 1 h. After the reaction was completed, the mixture was stirred and washed with pure water for 3 times, each time for 3 h, and then stirred and washed with 100% by volume ethanol for 3 times, each time for 3 h, to obtain a cross-linked porous resin containing tertiary amine groups, wherein the mass ratio of the epoxy group-containing cross-linked porous resin, water and N, N-dimethyl-1, 3-propylenediamine was 1:4:0.1;

[0102] (5) The cross-linked porous resin containing tertiary amine groups obtained in step (4) is mixed with 600 g of solvent (300 g of ethanol and 300 g of acetone), 12 g of 1,3-propane sultone is added, and a quaternization reaction is carried out at 60° C. for 12 h. The mixture is stirred and washed 5 times with a 75% by volume ethanol solution for 3 h each time, and then dried at 80° C. to obtain a cross-linked zwitterion modified adsorbent, wherein the mass ratio of the cross-linked porous resin containing tertiary amine groups, the solvent and 1,3-propane sultone is 1:6:0.12.

[0103] The microscopic appearance of the epoxy group-containing cross-linked porous resin prepared in step (3) of Example 1 is as follows: Figure 1 As shown, from Figure 1 It can be seen that the epoxy group-containing cross-linked porous resin prepared in step (3) of Example 1 is white smooth spherical particles with a particle size between 0.1 and 1 mm.

[0104] The microscopic appearance of the cross-linked zwitterion modified adsorbent prepared in Example 1 is as follows: Figure 2 As shown. Figure 2 It can be seen that the cross-linked zwitterion modified adsorbent prepared in Example 1 is white smooth spherical particles with a particle size between 0.1 and 1 mm.

[0105] The infrared spectrum of the cross-linked zwitterion modified adsorbent prepared in Example 1 is as follows: Figure 3 As shown. Figure 3 It can be seen that at 1038cm -1 The infrared characteristic peak of the sulfonate group appearing at 400 nm belongs to the zwitterionic group of sulfonamide betaine, indicating that the resin was successfully modified to obtain a zwitterionic group structure through Example 1.

[0106] Example 2

[0107] (1) to (3) are the same as in Example 1, to obtain a cross-linked porous resin containing epoxy groups;

[0108] (4) 100 g of the cross-linked porous resin containing epoxy groups prepared in step (3) was mixed with 500 g of a solvent (300 g of water and 200 g of ethanol), 20 g of N,N-dimethyl-1,3-propylenediamine was added, and a ring-opening addition reaction was carried out at 60° C. for 24 h. After the reaction was completed, the mixture was stirred and washed with pure water for 4 times, each time for 3 h, and then stirred and washed with a 95% volume concentration ethanol solution for 4 times, each time for 3 h, to obtain a cross-linked porous resin containing tertiary amine groups, wherein the mass ratio of the cross-linked porous resin containing epoxy groups, the solvent and N,N-dimethyl-1,3-propylenediamine was 1:5:0.2;

[0109] (5) The cross-linked porous resin containing tertiary amine groups obtained in step (4) is mixed with 500 g of ethanol, 10 g of sodium chloroacetate is added, and a quaternization reaction is carried out at 35° C. for 24 h. The mixture is stirred and washed four times with an ethanol solution having a volume concentration of 85%, each time for 3 h, and then dried at 40° C. to obtain a cross-linked zwitterion modified adsorbent, wherein the mass ratio of the cross-linked porous resin containing tertiary amine groups, ethanol and sodium chloroacetate is 1:5:0.1.

[0110] The cross-linked zwitterion modified adsorbent prepared in Example 2 is white smooth spherical particles with a particle size between 0.1 and 1 mm.

[0111] Example 3

[0112] (1) to (3) are the same as in Example 1, to obtain a cross-linked porous resin containing epoxy groups;

[0113] (4) 100 g of the cross-linked porous resin containing epoxy groups prepared in step (3) was mixed with 500 g of water, 50 g of N, N-dimethyl-1, 3-propylenediamine was added, and a ring-opening addition reaction was carried out at 20° C. for 48 h. After the reaction was completed, the mixture was stirred and washed with pure water for 3 times, each time for 3 h, and then stirred and washed with 95% ethanol solution for 5 times, each time for 3 h, to obtain a cross-linked porous resin containing tertiary amine groups, wherein the mass ratio of the cross-linked porous resin containing epoxy groups, water and N, N-dimethyl-1, 3-propylenediamine was 1:5:0.5;

[0114] (5) The cross-linked porous resin containing tertiary amine groups obtained in step (4) is mixed with 100 g of acetone, 15 g of β-propiolactone is added, and a quaternization reaction is carried out at 45° C. for 8 h. The mixture is stirred and washed 5 times with a 95% by volume ethanol solution for 3 h each time, and then dried at 60° C. to obtain a cross-linked zwitterionic modified adsorbent, wherein the mass ratio of the cross-linked porous resin containing tertiary amine groups, acetone and β-propiolactone is 1:1:0.15.

[0115] The cross-linked zwitterion modified adsorbent prepared in Example 3 is white smooth spherical particles with a particle size between 0.1 and 1 mm.

[0116] Example 4

[0117] (1) 100 g of divinylbenzene (DVB 80), 10 g of glycidyl methacrylate, 140 g of a porogen (80 g of xylene, 60 g of isooctyl alcohol) and 1.1 g of benzoyl peroxide were mixed to obtain an oil phase, wherein the mass ratio of divinylbenzene, glycidyl methacrylate, the porogen and the benzoyl peroxide was 1:0.1:1.4:0.011;

[0118] (2) mixing 600 g of water and 12 g of gelatin to obtain an aqueous phase, wherein the mass ratio of water to gelatin is 1:0.02;

[0119] (3) adding the oil phase obtained in step (1) to the water phase obtained in step (2) (the mass ratio of the oil phase to the water phase is 1:2.4), and performing suspension polymerization at 82° C. for 4 h. After the reaction is completed, washing with a 95% by volume ethanol solution for 3 times, each time for 3 h, and then drying at 60° C. to obtain a cross-linked porous resin containing epoxy groups;

[0120] (4) 100 g of the cross-linked porous resin containing epoxy groups prepared in step (3) was mixed with 700 g of a solvent (100 g of water and 600 g of acetone), 50 g of polyethyleneimine (average molecular weight 300) was added, and a ring-opening addition reaction was carried out at 50° C. for 32 h. After the reaction was completed, the mixture was stirred and washed with pure water for 4 times, each time for 3 h, and then stirred and washed with 100% by volume ethanol for 3 times, each time for 3 h, to obtain a cross-linked porous resin containing tertiary amine groups, wherein the mass ratio of the cross-linked porous resin containing epoxy groups, the solvent and the polyethyleneimine was 1:7:0.5;

[0121] (5) The cross-linked porous resin containing tertiary amine groups obtained in step (4) is mixed with 500 g of ethanol, 10 g of 1,3-propane sultone is added, and a quaternization reaction is carried out at 80° C. for 6 h. The mixture is stirred and washed four times with a 95% by volume ethanol solution for 3 h each time, and then dried at 60° C. to obtain a cross-linked zwitterion modified adsorbent, wherein the mass ratio of the cross-linked porous resin containing tertiary amine groups, ethanol and 1,3-propane sultone is 1:5:0.1.

[0122] The cross-linked porous resin containing epoxy groups prepared in step (3) of Example 4 is white smooth spherical particles with a particle size between 0.1 and 1 mm.

[0123] The cross-linked zwitterion modified adsorbent prepared in Example 4 is white smooth spherical particles with a particle size between 0.1 and 1 mm.

[0124] Example 5

[0125] (1) 100 g of a styrene monomer (10 g of styrene, 90 g of divinylbenzene (DVB 55)), 20 g of glycidyl acrylate, 50 g of a porogen (methyl isobutyl carbinol) and 3 g of azobisisobutyronitrile were mixed to obtain an oil phase, wherein the mass ratio of the styrene monomer, glycidyl acrylate, the porogen and the azobisisobutyronitrile was 1:0.2:0.5:0.03;

[0126] (2) 500 g of water and 3 g of polyvinyl alcohol (1788) were mixed to obtain an aqueous phase, wherein the mass ratio of water to gelatin was 1:0.006;

[0127] (3) adding the oil phase obtained in step (1) to the water phase obtained in step (2) (the mass ratio of the oil phase to the water phase is 1:2.9), and performing suspension polymerization at 76° C. for 24 h. After the reaction is completed, stirring and washing with a 90% by volume ethanol solution for 4 times, each time for 3 h, and then drying at 75° C. to obtain a cross-linked porous resin containing epoxy groups;

[0128] (4) 100 g of the epoxy group-containing cross-linked porous resin prepared in step (3) was mixed with 200 g of a solvent (100 g of water and 100 g of methanol), 60 g of polyethyleneimine (average molecular weight 600) was added, and a ring-opening addition reaction was carried out at 40° C. for 24 h. After the reaction was completed, the mixture was stirred and washed with pure water for 5 times, each time for 3 h, and then stirred and washed with a 90% by volume ethanol solution for 5 times, each time for 3 h, to obtain a tertiary amine group-containing cross-linked porous resin, wherein the mass ratio of the epoxy group-containing cross-linked porous resin, the solvent and the polyethyleneimine was 1:2:0.6;

[0129] (5) The cross-linked porous resin containing tertiary amine groups obtained in step (4) is mixed with 200 g of methanol, 40 g of β-propiolactone is added, and a quaternization reaction is carried out at 20° C. for 24 h. The mixture is stirred and washed with 100% ethanol by volume for 3 times, each time for 3 h, and then dried at 80° C. to obtain a cross-linked zwitterionic modified adsorbent, wherein the mass ratio of the cross-linked porous resin containing tertiary amine groups, methanol and β-propiolactone is 1:2:0.4.

[0130] The cross-linked porous resin containing epoxy groups prepared in step (3) of Example 5 is white smooth spherical particles with a particle size between 0.1 and 1 mm.

[0131] The cross-linked zwitterion modified adsorbent prepared in Example 5 is white smooth spherical particles with a particle size between 0.1 and 1 mm.

[0132] Example 6

[0133] 30g of the cross-linked zwitterion modified adsorbent prepared in Example 1, 15g of triethyl orthoformate, 200g of ethylene dichloride and 15g of ferric chloride were mixed evenly, and after swelling, a post-crosslinking reaction was carried out at 80°C for 8h. After the reaction was completed, a 2% hydrochloric acid solution was first used for stirring and washing for 4h, and then a 1.5% sodium hydroxide solution was used for stirring and washing for 6h, and then washed with water until neutral, and finally a 95% ethanol solution was used for elution for 10h, and then dried at 70°C to obtain an ultra-high cross-linked zwitterion modified adsorbent, wherein the mass ratio of the cross-linked zwitterion modified adsorbent, triethyl orthoformate, ethylene dichloride and ferric chloride was 1:0.5:6.7:0.5.

[0134] The microscopic appearance of the ultra-high cross-linked zwitterion modified adsorbent prepared in Example 6 is as follows: Figure 4 As shown. Figure 4 It can be seen that the ultra-high cross-linked zwitterion modified adsorbent prepared in Example 6 is brown smooth spherical particles with a particle size between 0.1 and 1 mm.

[0135] Example 7

[0136] 30g of the cross-linked zwitterion modified adsorbent prepared in Example 2, 10g of a small molecule cross-linking agent (5g of diethoxymethane, 5g of aminoacetaldehyde diethyl acetal), 300g of ethylene dichloride and 10g of ferric chloride were mixed evenly, and after swelling, a post-cross-linking reaction was carried out at 80°C for 12h. After the reaction was completed, the mixture was first washed with a 0.5% hydrochloric acid solution under stirring for 24h, and then washed with a 0.5% sodium hydroxide solution under stirring for 24h, and then washed with water until neutral, and finally rinsed with 100% ethanol by volume for 10h, and then dried at 80°C to obtain an ultra-high cross-linked zwitterion modified adsorbent, wherein the mass ratio of the cross-linked zwitterion modified adsorbent, the small molecule cross-linking agent, ethylene dichloride and ferric chloride was 1:0.3:10:0.3.

[0137] The ultra-high cross-linked zwitterion modified adsorbent prepared in Example 7 is dark brown smooth spherical particles with a particle size between 0.1 and 1 mm.

[0138] Example 8

[0139] 30g of the cross-linked zwitterion modified adsorbent prepared in Example 3, 13g of a small molecule cross-linking agent (10g of formaldehyde dimethyl acetal, 3g of N,N-dimethylformamide dimethyl acetal), 100g of ethylene dichloride and 15g of ferric chloride were mixed evenly, and after swelling, a post-cross-linking reaction was carried out at 85°C for 3h. After the reaction was completed, it was first washed with a 0.2% hydrochloric acid solution with stirring for 24h, and then washed with a 5% sodium hydroxide solution with stirring for 1h, and then washed with water until neutral, and finally rinsed with a 70% ethanol solution with a volume concentration for 10h, and then dried at 40°C to obtain an ultra-high cross-linked zwitterion modified adsorbent, wherein the mass ratio of the cross-linked zwitterion modified adsorbent, the small molecule cross-linking agent, ethylene dichloride and ferric chloride was 1:0.4:3.3:0.5.

[0140] The ultra-high cross-linked zwitterion modified adsorbent prepared in Example 8 is brown smooth spherical particles with a particle size between 0.1 and 1 mm.

[0141] Example 9

[0142] 30g of the cross-linked zwitterion modified adsorbent prepared in Example 4, 10g of a small molecule cross-linking agent (4-aminobutyraldehyde dimethyl acetal), 300g of dichloromethane and 60g of ferric chloride were mixed evenly, and after swelling, a post-crosslinking reaction was carried out at 75°C for 48h. After the reaction was completed, the mixture was first washed with a 1.5% hydrochloric acid solution with stirring for 12h, then washed with a 1% sodium hydroxide solution with stirring for 12h, then washed with water until neutral, and finally rinsed with a 95% ethanol solution with a volume concentration of 5h, and then dried at 50°C to obtain an ultra-high cross-linked zwitterion modified adsorbent, wherein the mass ratio of the cross-linked zwitterion modified adsorbent, the small molecule cross-linking agent, dichloromethane and ferric chloride was 1:0.3:10:2.

[0143] The ultra-high cross-linked zwitterion modified adsorbent prepared in Example 9 is brown smooth spherical particles with a particle size between 0.1 and 1 mm.

[0144] Example 10

[0145] 30g of the cross-linked zwitterion modified adsorbent prepared in Example 5, 3g of a small molecule cross-linking agent (diethoxymethane), 200g of nitrobenzene and 0.6g of aluminum chloride were mixed evenly, and after swelling, a post-crosslinking reaction was carried out at 50°C for 12h. After the reaction was completed, the mixture was first washed with 8% hydrochloric acid solution with stirring for 1h, then washed with 5% sodium hydroxide solution with stirring for 1h, then washed with water until neutral, and finally rinsed with 90% ethanol solution by volume for 8h, and then dried at 80°C to obtain an ultra-high cross-linked zwitterion modified adsorbent, wherein the mass ratio of the cross-linked zwitterion modified adsorbent, the small molecule cross-linking agent, nitrobenzene and aluminum chloride was 1:0.1:6.7:0.02.

[0146] The microscopic appearance of the ultra-high cross-linked zwitterion modified adsorbent prepared in Example 10 is as follows: Figure 5 As shown. Figure 5 It can be seen that the ultra-high cross-linked zwitterion modified adsorbent prepared in Example 10 is dark brown smooth spherical particles with a particle size between 0.1 and 1 mm.

[0147] Comparative Example 1

[0148] (1) 105 g of divinylbenzene (DVB 80), 160 g of a porogen (80 g of toluene, 80 g of n-heptane) and 2 g of benzoyl peroxide were mixed to obtain an oil phase, wherein the mass ratio of divinylbenzene, porogen and benzoyl peroxide was 1:1.5:0.02;

[0149] (2) mixing 400 g of water and 10 g of gelatin to obtain an aqueous phase, wherein the mass ratio of water to gelatin is 1:0.025;

[0150] (3) adding the oil phase obtained in step (1) to the water phase obtained in step (2) (the mass ratio of the oil phase to the water phase is 1:1.5), and performing suspension polymerization at 80° C. for 12 h. After the reaction is completed, the cross-linked porous resin is obtained by purification and drying.

[0151] The cross-linked porous resin prepared in Comparative Example 1 is white smooth spherical particles with a particle size between 0.1 and 1 mm.

[0152] Comparative Example 2

[0153] 30g of the cross-linked porous resin prepared in Comparative Example 1, 10g of a small molecule cross-linking agent (5g of diethoxymethane, 5g of aminoacetaldehyde diethyl acetal), 300g of ethylene dichloride and 10g of ferric chloride were evenly mixed, swollen, and then post-cross-linked at 80°C for 12h, purified, and dried to obtain an ultra-high cross-linked adsorbent, wherein the mass ratio of the cross-linked porous resin, the small molecule cross-linking agent, ethylene dichloride and ferric chloride was 1:0.3:10:0.3.

[0154] The ultra-high cross-linked adsorbent prepared in Comparative Example 2 is brown smooth spherical particles with a particle size between 0.1 and 1 mm.

[0155] The adsorbents prepared in test examples 1 to 10, the adsorbents prepared in comparative examples 1 to 2, and the commercial perfusion resin CytoSorb TM The hydrophilicity of the adsorbent and the perfusion resin HA130 adsorbent is shown in Table 1. Hydrophilicity evaluation: The adsorbent was dried and gently sprinkled in a beaker of pure water. The floating and sinking of the adsorbent in the pure water were visually observed to determine its hydrophilicity.

[0156] Table 1 Adsorbents prepared in Examples 1 to 10, adsorbents prepared in Comparative Examples 1 to 2, and commercial perfusion resin CytoSorb TM Hydrophilicity of adsorbent and perfusion resin HA130 adsorbent

[0157]

[0158]

[0159] It can be seen from Table 1 that the adsorbents prepared in Examples 1 to 10 of the present invention can all sink rapidly into water, showing super hydrophilicity.

[0160] The adsorbents prepared in test examples 1 to 10, the adsorbents prepared in comparative examples 1 to 2, and the commercial perfusion resin CytoSorb TMBlood compatibility of adsorbent and perfusion resin HA130 adsorbent. The present invention evaluates the blood compatibility of adsorbent materials through performance indicators such as protein adsorption rate, hemolysis rate, and platelet count test. The values ​​of protein adsorption rate, hemolysis rate, and platelet reduction rate can directly reflect the blood compatibility of the material; lower values ​​reflect better blood compatibility.

[0161] in:

[0162] Protein adsorption rate test: The adsorbent was washed 5 times with saline, and the washed sample was tested at a bath ratio of 1mL / 10mL. The adsorbent was in dynamic contact with plasma at 170r / min at 37°C for 120min, and the albumin and total protein content before and after adsorption was detected, and the adsorption rate was calculated.

[0163] Hemolysis rate test: The adsorbent was washed with saline for 5 times, and the washed sample was tested at a bath ratio of 5g / 10mL. The adsorbent was incubated with diluted rabbit blood at 37°C, and the absorbance of hemoglobin released by red blood cell rupture was detected to calculate the hemolysis rate.

[0164] Platelet count test: The adsorbent was washed 5 times with saline, and the washed sample was tested at a bath ratio of 0.2 g / mL. The adsorbent was in dynamic contact with whole blood at 37°C at 30 r / min for 60 min, and the number of platelets in the whole blood was detected using a blood cell analyzer, and the platelet decrease rate was calculated.

[0165] The blood compatibility index evaluation test results of different adsorbents are shown in Table 2.

[0166] Table 2 Adsorbents prepared in Examples 1 to 10, adsorbents prepared in Comparative Examples 1 to 2, and commercial perfusion resin CytoSorb TM Blood compatibility test results of adsorbent and cartridge resin HA130 adsorbent

[0167]

[0168] As can be seen from Table 2, the adsorbents prepared in Examples 1 to 10 of the present invention have albumin adsorption rates less than 1%, hemolysis rates ≤ 0.1%, and platelet reduction rates less than 8.5%. TM The adsorbent and HA130 resin, the embodiments of the present invention show good blood compatibility. At the same time, the adsorbents of Examples 1 to 10 of the present invention were tested for biocompatibility such as cytotoxicity, thrombosis, coagulation, complement activation, immunity, etc., and all showed excellent blood compatibility results.

[0169] Adsorption performance evaluation

[0170] 10 mL of plasma solution containing β2-microglobulin (β2-MG), interleukin-6 (IL-6), p-cresol sulfate PCS, indoxyl sulfate IS, indoleacetic acid IAA, hippuric acid HA, and bilirubin were added to the adsorbent prepared in Examples 1 to 10, the adsorbent prepared in Comparative Examples 1 to 2, and the commercial perfusion resin CytoSorb TM 1 mL of the adsorbent, perfusion resin HA130 adsorbent, and BS resin adsorbent were shaken at 37°C for 2 hours, and the changes in the adsorbed substances were measured. The results are shown in Table 3.

[0171] Table 3 Adsorbents prepared in Examples 1 to 10, adsorbents prepared in Comparative Examples 1 to 2, and commercial perfusion resin CytoSorb TM Toxin adsorption performance of adsorbent, perfusion resin HA130 adsorbent and BS resin adsorbent

[0172]

[0173] By comparing the examples with the comparative examples in Table 3, it can be seen that the adsorbents prepared in Examples 1 to 10 of the present invention all maintain a relatively high adsorption rate of β2-microglobulin (β2-MG) and interleukin IL-6, and are even better than CytoSorb TM Adsorbent and HA130 resin.

[0174] In addition, the adsorbents prepared in Examples 4, 5, 7, 8, 9, 10 and Comparative Example 2 of the present invention have good adsorption performance for protein-bound toxins such as p-cresol sulfate PCS, indoxyl sulfate IS, indoleacetic acid IAA, hippuric acid HA, and bilirubin, which are significantly better than CytoSorb TM Adsorbent and HA130 resin. In addition, the test found that the adsorbents prepared in Examples 4, 5, 7, 8, 9, 10 and Comparative Example 2 of the present invention also have good adsorption properties for bile acid, endotoxin, etc.

[0175] In summary, the adsorbent prepared by the present invention has excellent hydrophilicity, ultra-low protein adsorption, excellent adsorption performance for toxins and excellent blood compatibility.

[0176] The resin adsorbent prepared in the embodiment of the present invention is further prepared into a hemoperfusion device, which can be used for clinical treatment of diseases and conditions such as renal failure, liver failure, acute poisoning, sepsis and septicemia, autoimmune diseases, inflammatory diseases, and hyperlipidemia.

[0177] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a cross-linked zwitterion modified adsorbent, comprising the following steps: (1) mixing a styrene monomer, an epoxy group-containing monomer, a porogen and an initiator to obtain an oil phase; (2) mixing the dispersant and water to obtain an aqueous phase; (3) mixing the oil phase obtained in step (1) and the water phase obtained in step (2) to carry out suspension polymerization to obtain a cross-linked porous resin containing epoxy groups; (4) mixing the epoxy group-containing cross-linked porous resin obtained in step (3), the first solvent and the amino compound, and performing a ring-opening addition reaction to obtain a tertiary amine group-containing cross-linked porous resin; (5) mixing the cross-linked porous resin containing tertiary amine groups obtained in step (4), a second solvent and a quaternary ammonium reagent, and performing a quaternary ammonium reaction to obtain a cross-linked zwitterion-modified adsorbent; There is no chronological order for steps (1) and (2).

2. The preparation method according to claim 1, characterized in that: In the step (1), the mass ratio of the styrene monomer, the epoxy-containing monomer, the porogen and the initiator is 1: (0.05-1): (0.3-3): (0.005-0.05).

3. The preparation method according to claim 1, characterized in that: The mass ratio of water to dispersant in the step (2) is 1:(0.001-0.06).

4. The preparation method according to claim 1, characterized in that: The mass ratio of the oil phase to the water phase in the step (3) is 1:(1-5).

5. The preparation method according to claim 1, characterized in that: The temperature of the suspension polymerization in step (3) is 60 to 90° C., and the time of the suspension polymerization is 4 to 24 hours.

6. The preparation method according to claim 1, characterized in that: The temperature of the ring-opening addition reaction in step (4) is 20 to 80° C., and the time of the ring-opening addition reaction is 1 to 48 hours.

7. The cross-linked zwitterion modified adsorbent prepared by the preparation method according to any one of claims 1 to 6.

8. A method for preparing an ultra-high cross-linked zwitterion modified adsorbent, comprising the following steps: The cross-linked zwitterion modified adsorbent according to claim 7, a small molecule cross-linking agent, a third solvent and a catalyst are mixed and subjected to a post-cross-linking reaction to obtain an ultra-high cross-linked zwitterion modified adsorbent.

9. The ultra-high cross-linked zwitterion modified adsorbent prepared by the preparation method of claim 8.

10. A blood perfusion device comprising the cross-linked zwitterion modified adsorbent according to claim 7 or the ultra-high cross-linked zwitterion modified adsorbent according to claim 9.

Citation Information

Patent Citations

  • Blood purification adsorbent and its preparation method

    CN105348541B